Parasitic Disease Education in Selacai Village Community Cipaku District Ciamis Regency - Ary Nurmalasari; Rahma Anggi Putri Pertiwi; Niva Puspita; Ai Resa Nuraeni; Bilal Ali Faturrahman; M.Fahreza Kencana; Setiofani Utami; Katya Gifanovia; Epi Amalia (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: Parasitic diseases are still largely unknown and often overlooked. Objective: The purpose of carrying out community service activities in the form of PPKM (Public Health Development Practices) is to increase public awareness of the importance of health. This activity is also carried out to help by introducing parasitic diseases to the people of Ciheras Hamlet, Selacai Village so that they are more responsive and dangerous of parasitic diseases, and are able to apply a clean and healthy lifestyle. Method: The method is carried out by observation, namely looking at the description of the environment around Ciheras Hamlet, Selacai Village. Result: In the PPKM program carried out in Ciheras Hamlet, Selacai Village, education was carried out using an approach in the form of recitation and provision of material displayed in a power point about parasitic diseases (helminthiasis). Conclusion: All work programs have been successfully carried out with full support by the community.